Students’ Engagement in STEAM PjBL-Design Thinking for Environmental Literacy - Rahmawati, Yuli; Irwanto, Irwanto; Mardiah, Alin; Taylor, Elisabeth; Taylor, Peter Charles; Lisdiana, Hayyun; Syaadah, Rika Siti (Journal of Education Culture and Society, 2025)
Aim. The aim of this study was to investigate Indonesian students’ engagement in STEAM Project-Based Learning (PjBL), integrated with design thinking, to enhance their environmental literacy. Methods. A survey was conducted with a sample of 156 eleventh-grade students from five classrooms in three secondary schools in Jakarta, Indonesia. The study used The Environmental Literacy Scale (ELS) to measure cognitive, affective, and behavioural elements of environmental literacy, and an interview was conducted to evaluate students’ views. A paired t-test and thematic analysis were used to analyse the data. Results. The study revealed that students exhibited moderate cognitive, affective, and behavioural elements of environmental literacy. Contextual learning through STEAM PjBL-design thinking effectively enhanced students’ knowledge and behaviour and their positive attitude toward environmental issues. Female students were found to generally outperform male students in cognitive and affective elements, while both genders demonstrated similar environmental behaviour. Conclusion. In conclusion, integrating STEAM-PjBL with design thinking can positively impact students’ environmental literacy and their engagement in chemistry. The findings suggest practical implications for enhancing interdisciplinary learning in chemistry education to promote environmental sustainability.